THE THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE AND CARBON ACCOUNTING DISCLOSURE ON PROFITABILITY (CASE STUDY OF COMPANIES LISTED ON THE IDX IN THE INDUSTRIAL SECTOR 2021-2024) - Nurul Hidayah; Elsa Fitri Amran; Atika Amor (Jurnal Akuntansi Syariah (JAkSya), 2025)
This research is motivated by increasing attention to the environmental impact of industrial sector activities, particularly carbon emissions, and their impact on corporate profitability. The objective of this study is to examine the influence of environmental performance and accounting carbon disclosure on the profitability of industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The study uses a quantitative approach utilizing secondary data obtained through documentation of annual reports and company sustainability reports. The results of statistical analysis indicate that environmental-related practices demonstrate a measurable association with corporate financial performance, although the contribution of each variable differs in magnitude and significance. The findings suggest that strong environmental performance and effective carbon management practices may function as strategic signals that enhance investor perception and corporate value. Therefore, integrating environmental policies into corporate business strategies is essential for supporting long-term financial sustainability within the industrial sector.